KEBUDAYAAN POLITIK DAN KESUSASTRAAN INDONESIA: SEBUAH UPAYA PENELUSURAN - Budiman, Ajang (Jurnal Bestari, 1992)
Politics is an effort of society to obtain the authority and maintain it as log as possible. People through politics are able to govern the society of a country in rder to achieve nation's goals such as, welfare, prosperity and social justice. In the process of attaining the authority sometimes needs physical conflict between the members of political party, further more it may cause destruction. Many people say that politic is cruel, however, it is cruel or not, the politic of a country is influeced by people's culture themselves.